Implementación de un sistema ERP en la empresa Italpet S.A.C. - Sinforoso Loayza, Manuel Francisco (2022)
The present work details the improvement that was made in the company Italpet S.A.C. when an ERP system was implemented in 2018 in order to integrate the different areas of the company through software, thus achieving greater competitiveness in sales and resource management. Italpet S.A.C. is a company in the metalworking industry with a presence in the Peruvian market since 1999. It is dedicated to providing diverse solutions in the food and beverage industry, both in machinery and mechanical engineering services. For this work to implement an ERP system, the methodology of the seven steps of continuous improvement was used. First, the improvement opportunities were selected by analyzing the company internally and externally, and then as a second step to quantify and select the main problem in the company. As a third step, the root causes of the problem were analyzed using an Ishikawa diagram. The most critical was found through its frequency and impact on the main problem, and then the main root cause was identified through the Pareto diagram. In the fourth step, the main management indicators of the company's situation were identified, then a goal was proposed to improve those indicators with the solution to be implemented. The fifth step is to define and propose the solutions, in which the most suitable supplier was chosen to implement the solution and the activities schedule was carried out. As a sixth step, the implementation of the ERP was detailed and the benefits were evaluated qualitatively and quantitatively, presenting the new management indicators after the implementation of the improvement and analyzing the net economic flow. The seventh step of continuous improvement is to establish guarantee actions, for which constant training was carried out for the personnel and corrective actions were taken to the errors that appeared during the implementation of the new ERP.